The Characteristics, Prevalence, and Risk Factors of Drug-Induced Liver Injury Among Brucellosis Inpatients in Xinjiang, China - Tuohutaerbieke, Maermaer; Li, Xinjie; Yin, Yue; Chen, Wei; Wu, Dongmei; Mao, Zhize; Mamuerjiang, Jiamixi; Mao, Yimin; Shen, Tao (Frontiers in Pharmacology, 2021)
Background: We investigated the prevalence, demographic and clinical features, and risk factors associated with drug-induced liver injury (DILI) during the treatment of brucellosis inpatients in a retrospective study. Methods: We collected the clinical data of 782 brucellosis inpatients admitted at the Shawan County People's Hospital, Xinjiang, from 2015 to 2019. All cases were re-evaluated using the international consensus of DILI criteria and RUCAM rating scale. 71 patients were confirmed as DILI cases and compared with 523 other patients with normal liver function. Results: It was indicated that DILI occurred with a prevalence of about 9.08% among brucellosis inpatients receiving drug therapy. Hepatocellular injury was the most common type of DILI (61.97%, 95% confidence interval [CI] 50.34-72.37), followed by mixed (23.94%, 95% CI 15.52-35.04) and cholestatic types (14.08%, 95% CI 7.83-24.02). In addition, 13.64% of the hepatocellular DILI cases fulfilled Hy’s law criteria and only two cases (2.82%) progressed to severe DILI. Most patients adopted the combination of rifampicin, antipyretic analgesics, anti-infective agents, and traditional Chinese medicine for the treatment of brucellosis, with all the 71 patients taking rifampicin as the drug of choice. Multivariable logistic regression analyses indicated that obesity, regular alcohol intake, and decreased serum albumin were the independent risk factors of DILI in patients with brucellosis after adjusting for gender, age, and ethnicity. Conclusions: DILI occurred in a minority of inpatients diagnosed with brucellosis receiving rifampicin-based therapeutic regimen. In addition, obesity, alcohol abuse, and decreased serum albumin were valuable predictors of the risk of DILI in patients with brucellosis.